Blue Flashes as Counterparts to Narrow Bipolar Events: The Optical Signal of Shallow In‐Cloud Discharges. Issue 13 (30th June 2021) - Li, Dongshuai; Luque, Alejandro; Gordillo‐Vázquez, F. J.; Liu, Feifan; Lu, Gaopeng; Neubert, Torsten; Chanrion, Olivier; Zhu, Baoyou; Østgaard, Nikolai; Reglero, Víctor
Abstract: Narrow Bipolar Events (NBEs) are powerful radio emissions from thunderstorms, which have been recently associated with blue optical flashes on cloud tops and attributed to extensive streamer electrical discharges named fast breakdown. Combining data obtained from a thunderstorm over South China by the space‐based Atmosphere Space Interactions Monitor, the Vaisala GLD360 global lightning network and very low frequency/low frequency radio detectors, here we report and analyze for the first time the optical emissions of blue luminous events associated with negative NBEs and located at the top edge of a thundercloud. These emissions are weakly affected by scattering from cloud droplets, allowing us to estimate the source extension and optical energy involved in the process. The optical energy in the 337‐nm band emitted by fast breakdown is about 10 4 J, which involves around 10 9 streamer initiation events. Plain Language Summary: Installed on the International Space Station, the Atmosphere‐Space Interactions Monitor is designed to observe Earth thunderstorms from space. Often it detects bursts of blue light emerging from active thunderclouds. These detections have been previously linked to radio signals named narrow bipolar events (NBEs) that are routinely detected during a thunderstorm. Here we analyze the blue flashes from a storm that profusely produced negative‐polarity NBEs. The optical signal can be understood as being produced by extended events close to the cloud top and we show that it is consistent with the barely understood electrical discharge process called fast breakdown that involves a huge number of thin, bright filaments called streamers. Key Points: Negative‐polarity narrow bipolar events are typically associated with extended optical sources at the edge of a thundercloud Thermal emissions in the oxygen 777 nm band are absent or very weak, indicating non‐thermal processes The optical energy in the 337 nm band is about 10 4 J, which requires around 10 9 streamers